2021
DOI: 10.1177/21501327211029816
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Yearlong Diabetes Prevention Program-Based Lifestyle Intervention on Cardiovascular Health Metrics

Abstract: Introduction The American Heart Association created “Life’s Simple Seven” metrics to estimate progress toward improving US cardiovascular health in a standardized manner. Given the widespread use of federally funded Diabetes Prevention Program (DPP)-based lifestyle interventions such as the Group Lifestyle Balance (DPP-GLB), evaluation of change in health metrics within such a program is of national interest. This study examined change in cardiovascular health metric scores during the course of a yearlong DPP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Clearly, altered glucose metabolism as manifested by hyperglycemia at the start of the weight reduction program had detrimental impact on the entire weight loss process. These observations are consistent with the notion that the impact of lifestyle intervention on diabetes prevention cannot be solely ascribed to the body weight reduction [ 39 ]. It should also by noted that WC, AC, and AMC diminished in both normoglycemic and hyperglycemic patients following the weight reduction program.…”
Section: Discussionsupporting
confidence: 91%
“…Clearly, altered glucose metabolism as manifested by hyperglycemia at the start of the weight reduction program had detrimental impact on the entire weight loss process. These observations are consistent with the notion that the impact of lifestyle intervention on diabetes prevention cannot be solely ascribed to the body weight reduction [ 39 ]. It should also by noted that WC, AC, and AMC diminished in both normoglycemic and hyperglycemic patients following the weight reduction program.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, continuous intervention reduces the risk of lifestylerelated diseases. It was reported that long-term intervention influenced cardiovascular health parameters [25].…”
Section: Parameters Of Lifestyle-related Diseases In the Persons Who ...mentioning
confidence: 99%
“…A year-long community support program focusing on diabetes prevention and cardiovascular health found significant improvements in five continuously measured risk factors. 7 The program also led to beneficial changes in body mass index, activity levels, and blood pressure distributions among participants. 7 Despite the demonstrated effectiveness of community diabetes support and education programs, persistent barriers impede patient enrollment in these initiatives.…”
Section: Introductionmentioning
confidence: 99%
“…7 The program also led to beneficial changes in body mass index, activity levels, and blood pressure distributions among participants. 7 Despite the demonstrated effectiveness of community diabetes support and education programs, persistent barriers impede patient enrollment in these initiatives.…”
Section: Introductionmentioning
confidence: 99%